(untitled) (Research, Society and Development, 2022)
Objective: To discuss the HIV epidemic in young adults, residents of the municipalities of the Second Health Regional of Paraná, notified in the period 2007-2015. Methodology: Ecological retrospective study. Data were collected from public websites to characterize the territory and the way of life of the local population. The information of the notifications was collected in SINAN-Net. The category of analysis was the way of living in the territory anchored in the assumptions of Critical Epidemiology. Results: We identified 2,482 notifications in adults aged 20-29 years, of these 2,376 (95.7%) were cases of HIV and 106 (4.3%) cases of AIDS. It is noteworthy that 74.3% of the individuals were white and 95.9% lived in urban areas. As for the individual’s occupation, 59.1% of the notifications had the field not filled in/ignored. Final considerations: The HIV phenomenon in young people showed the highest prevalence rates in the municipalities with the worst social indicators and the municipalities that had the best infrastructure of health services recorded the highest number of cases in the period. Intersectoral actions that reflect on the economic indicators of societies and the epidemiological indices, individual and collective behaviors are necessary to confront the phenomenon.